Alternatives of Corporate Restructuring In The Agriculture of the Peruvian Coast - Valdivia H., Martín (1987)
In this article, the author analyzes three of the various alternatives of organizational restructuring which have been proposed for the Worker 's Agrarian Cooperatives of the Peruvian coast, stressing in the possibilities of each of them to solve the main internal problems of this kind of business organizations. Likewise, the author identifies the main internal problems which, linked to external factors, have led to the Cooperatives' crisis and their desintegration into individual plots. He also discusses, at a theoretical level, the advantages and disadvantages of a family plot model, vis-a-vis the cooperative one. Finally, he analyzes three restructuring options ("sectorization" -smaller-sizes cooperatives-, service cooperatives and "worker 's partnerships"), as mechanisms that may overcome the Cooperatives' inherent problems, while maintaining their advantages, such as economies of scale.